2017
DOI: 10.5194/acp-2016-1113
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Power Plant Fuel Switching and Air Quality in a Tropical Forested Environment

Abstract: <p><strong>Abstract.</strong> How a changing energy matrix for power production affects air quality is considered for an urban region in a tropical, forested environment. Manaus, the largest city in the central Amazon basin of Brazil, is in the process of changing its fossil fuel power energy matrix from entirely fuel oil and diesel to nearly entirely natural gas across an approximately ten-year period. Three scenarios of urban air quality, specifically afternoon ozone… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…In addition, a companion study by Medeiros et al (2017) focuses on how the changing energy matrix for power production affects air quality in the Manaus region. Both studies were conducted using the Weather Research and Forecasting with Chemistry (WRF-Chem) model, where the simulations for diverse scenarios were performed according to the current conditions of the region.…”
Section: S a Abou Rafee Et Al: Contributions Of Mobile Stationarymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a companion study by Medeiros et al (2017) focuses on how the changing energy matrix for power production affects air quality in the Manaus region. Both studies were conducted using the Weather Research and Forecasting with Chemistry (WRF-Chem) model, where the simulations for diverse scenarios were performed according to the current conditions of the region.…”
Section: S a Abou Rafee Et Al: Contributions Of Mobile Stationarymentioning
confidence: 99%
“…This indicates that the TPPs are mainly responsible for the high concentrations of most chemical species in the grid. The influence of matrix change is discussed in the companion paper of Medeiros et al (2017), and more details can found in this paper.…”
Section: Mean and Peak Behavior Of Pollutantsmentioning
confidence: 99%
“…Organic compounds comprise up to 90 % of the mass concentration of submicron organic particulate matter (PM) over tropical forests (Kanakidou et al, 2005). Submicron PM has adverse effects on human health (Nel, 2005;Pope III and Dockery, 2006) and influences air quality and climate by scattering radiation and acting as cloud condensation nuclei (Ramanathan et al, 2001;Kaufman et al, 2002). A significant fraction of the submicron organic material originates from secondary processes, mainly by the atmospheric oxidation of volatile organic compounds (VOCs) emitted as part of natural and human activities (Zhang et al, 2007;Hallquist et al, 2009;Jimenez et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Organic compounds comprise up to 90 % of the mass concentration of submicron organic particulate matter (PM) over tropical forests (Kanakidou et al, 2005). Submicron PM has adverse effects on human health (Nel, 2005;Pope III and Dockery, 2006) and influences air quality and climate by scattering radiation and acting as cloud condensation nuclei (Ramanathan et al, 2001;Kaufman et al, 2002). A significant fraction of the submicron organic material originates from secondary processes, mainly by the atmospheric oxidation of volatile organic compounds (VOCs) emitted as part of natural and human activities Hallquist et al, 2009;Jimenez et al, 2009).…”
Section: Introductionmentioning
confidence: 99%